Assessing the Negative Impact of Palm Oil Industry in Malaysia through a Systemic Method - Ming, Lau Kai; Faiz, Mohd Turan; Norazlianie, Sazali (Semarak Ilmu Publishing, 2024)
This research paper studies the life cycle assessment of palm oil production and the impact on the environment due to palm oil production. A life cycle assessment includes a life cycle inventory and a life cycle impact assessment. The life cycle inventory accounts for all the parameters of the milling process of palm oil production, such as kernels, shells, etc. The life cycle impact assessment includes all the impacts on the environment and human health, such as global warming, ecotoxicity, radiation, the ozone layer, and more. This research paper will also include the opportunity to overcome the impacts due to palm oil production.